Short and Midterm Outcomes in Patients With Acute Myocardial Infarction: Results of the Nationwide TURKMI Registry - SÜNBÜL, MURAT (SAGE PUBLICATIONS INC, 2021)
This recent Turkish Myocardial Infarction registry reported that guidelines are largely implemented in patients with acute myocardial infarction (MI) in Turkey. We aimed to obtain up-to-date information for short- and midterm outcomes of acute MI. Fifty centers were selected using probability sampling, and all consecutive patients with acute MI admitted to these centers (between November 1 and 16, 2018) were enrolled. Among 1930 (mean age 62 +/- 13 years, 26% female) patients, 1195 (62%) had non-ST segment elevation myocardial infarction (NSTEMI) and 735 (38%) had ST segment elevation myocardial infarction (STEMI). Percutaneous coronary intervention (PCI) was performed in 94.4% of patients with STEMI and 60.2% of those with NSTEMI. Periprocedural mortality occurred in 4 (0.3%) patients. In-hospital mortality was significantly higher in STEMI than in patients with NSTEMI (5.4% vs 2.9%, respectively; P = .006). However, the risk became slightly higher in the NSTEMI group at 1 year. Women with STEMI had a significantly higher in-hospital mortality compared with men (11.2% vs 3.8%; P < .001); this persisted at follow-up. In conclusion, PCI is performed in Turkey with a low risk of complications in patients with acute MI. Compared with a previous registry, in-hospital mortality decreased by 50% within 20 years; however, the risk remains too high for women with STEMI.
Keywords: myocardial infarction; outcome; mortality; percutaneous coronary intervention; registries; LONG-TERM MORTALITY; ACUTE ST-ELEVATION; GENDER-DIFFERENCES; FRENCH REGISTRY; SURVIVAL; DESIGN; STEMI